Green in Software Engineering - Calero, Coral; Piattini, Mario; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This is the first book that presents a comprehensive overview of sustainability aspects in software engineering. Its format follows the structure of the SWEBOK and covers the key areas involved in the incorporation of green aspects in software engineering, encompassing topics from requirement elicitation to quality assurance and maintenance, while also considering professional practices and economic aspects. The book consists of thirteen chapters, which are structured in five parts. First the Introduction gives an overview of the primary general concepts related to Green IT, discussing what Green in Software Engineering is, and how it differs from Green by Software Engineering. Next Environments, Processes and Construction presents green software development environments, green software engineering processes, and green software construction in general. The third part, Economic and Other Qualities, details models for measuring how well software supports green software engineering techniques, and for performing trade-off analyses between alternative green practices from an economic perspective. Software Development Process then details techniques for incorporating green aspects at various stages of software development, including requirements engineering, design, testing, and maintenance. In closing, Practical Issues addresses the repercussions of green software engineering on decision-making, stakeholder participation, and innovation management. The audience for this book includes software engineering researchers in academia and industry seeking to understand the challenges and impact of green aspects in software engineering, as well as practitioners interested in learning about the state of the art in Green in Software Engineering.
Part I Introduction -- 1 Introduction to Green in Software Engineering -- Part II Environments, Processes and Construction -- 2 Green Software Engineering Environments -- 3 Processes for Green and Sustainable Software Engineering -- 4 Constructing Green Software Services: from Service Models to Cloud-based Architecture -- Part III Economic and Other Qualities -- 5 Economic Aspects of Green ICT -- 6 Green Software Quality Factors -- Part IV Software Development Process -- 7 From Requirements Engineering to Green Requirements Engineering -- 8 Towards Green Software Testing -- 9 Green Software Maintenance -- 10 Green Software and Software Quality -- 11 Green Software Measurement -- Part V Practical Issues -- 12 A Decision Making Model for Adopting GreenICT Strategies -- 13 Participation and Open Innovation for Sustainable Software Engineering.
Keywords: Software engineering; Information Systems; Sustainable development; Management; Computer industry; Computer science; Software Engineering; Management of Computing and Information Systems; Sustainable Development; Innovation/Technology Management; The Computer Industry; Computers and Society